The Problem of Prison Overcrowding with a Focus on the Situation in the Republic of Serbia - Milica Simović (Revija za kriminologiju i krivično pravo)
In recent years of the 21st century, prison systems have faced an enormous increase in the number of inmates worldwide. Whether overcrowding has always been a problem or is a result of modern times is an interesting question that numerous theorists have attempted to answer by explaining this phenomenon from various aspects, pointing out possible causes, consequences, certain solutions, and characteristics of the population that characterize many prisons. There is also a significant social impact, as every society, regardless of social class, has its own opinion on the purpose of prisons and the population housed within them. How the prison population changes, what transformations it brings, and what possible ways exist to overcome prison overcrowding are key questions that the author addresses in the paper, emphasizing that overcrowding as a trend, judging by statistical data and numerous literature, threatens to exceed all capacities and inflict severe social, physical, and psychological consequences on the incarcerated.